Sequential submaximal training in elite male rowers does not result in amplified increases in interleukin-6 or hepcidin - Fensham, N. C.; McKay, A. K.; Tee, N.; Lundy, B.; Anderson, B.; Morabito, A.; Ross, M. L. R.; Burke, L. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
Previous research investigating single bouts of exercise have identified baseline iron status and circulating concentrations of interleukin-6 (IL-6) as contributors to the magnitude of postexercise hepcidin increase. The current study examined the effects of repeated training bouts in close succession on IL-6 and hepcidin responses. In a randomized, crossover design, 16 elite male rowers completed two trials, a week apart, with either high (1,000 mg) or low (<50 mg) calcium pre-exercise meals. Each trial involved two, submaximal 90-min rowing ergometer sessions, 2.5 hr apart, with venous blood sampled at baseline; pre-exercise; and 0, 1, 2, and 3 hr after each session. Peak elevations in IL-6 (approximately 7.5-fold, p < .0001) and hepcidin (approximately threefold, p < .0001) concentrations relative to baseline were seen at 2 and 3 hr after the first session, respectively. Following the second session, concentrations of both IL-6 and hepcidin remained elevated above baseline, exhibiting a plateau rather than an additive increase (2 hr post first session vs. 2 hr post second session, p = 1.00). Pre-exercise calcium resulted in a slightly greater elevation in hepcidin across all time points compared with control (p = .0005); however, no effect on IL-6 was evident (p = .27). Performing multiple submaximal training sessions in close succession with adequate nutritional support does not result in an amplified increase in IL-6 or hepcidin concentrations following the second session in male elite rowers. Although effects of calcium intake require further investigation, athletes should continue to prioritize iron consumption around morning exercise prior to exercise-induced hepcidin elevations to maximize absorption.